Peace Counseling for Grief Recovery: A Study of Its Effectiveness in Families of Coal Mine Drowning Victims in East Kalimantan - Qudsiyah, Siti Nurul Hajirotul; Saputra, Wahyu Nanda Eka; Santosa, Hardi (citeus, 2026)
This study examines the psychological impact of prolonged grief among families of coal mining pit drowning victims and evaluates the effectiveness of peace counseling as an intervention strategy. The study aims to assess whether structured counseling can reduce grief loss and support adaptive psychological adjustment. A quantitative quasi-experimental approach was employed using a Single Subject Research (SSR) A–B–A design involving two participants who were mothers of the victims. Data were collected using the Grief Losing Scale administered repeatedly across baseline (A1), intervention (B), and post-intervention (A2) phases. The intervention consisted of six structured peace counseling sessions focusing on emotional processing, reflection, and meaning reconstruction. The findings reveal a clear reduction in grief levels during the intervention phase, followed by stable patterns in the post-intervention phase, indicating both immediate and sustained effects. The results suggest that peace counseling effectively facilitates emotional regulation and supports the reconstruction of meaning in the grieving process. In conclusion, this study provides empirical support for the use of peace counseling as a targeted intervention for prolonged grief, particularly in contexts of traumatic loss, while highlighting the need for further research with larger samples and extended follow-up periods to enhance generalizability.